2004
DOI: 10.1172/jci200420138
|View full text |Cite
|
Sign up to set email alerts
|

Axonal degeneration in paraplegin-deficient mice is associated with abnormal mitochondria and impairment of axonal transport

Abstract: In several neurodegenerative diseases, axonal degeneration occurs before neuronal death and contributes significantly to patients’ disability. Hereditary spastic paraplegia (HSP) is a genetically heterogeneous condition characterized by selective degeneration of axons of the corticospinal tracts and fasciculus gracilis. HSP may therefore be considered an exemplary disease to study the local programs mediating axonal degeneration. We have developed a mouse model for autosomal recessive HSP due to mutations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
148
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(164 citation statements)
references
References 45 publications
12
148
2
2
Order By: Relevance
“…30 RSV has been proven to improve the overall metabolic health status in clinical trials for patients with metabolic disorders, 32 which may or may not be confirmed in currently ongoing clinical trials for AD and Friedreich ataxia (NCT01339884, NCT01504854, NCT00743743, NCT00678431). Therapeutic implications derived from this work may be potentially extended to other diseases such as multiple sclerosis, 65 amyotrophic lateral sclerosis 66 and some forms of HSP such as SPG7, 54 which share axonal degeneration as a primary component of clinical disability and oxidative stress/mitochondria impairment as the primary or early contributing pathogenic factors. Mouse strains.…”
Section: Discussionmentioning
confidence: 98%
“…30 RSV has been proven to improve the overall metabolic health status in clinical trials for patients with metabolic disorders, 32 which may or may not be confirmed in currently ongoing clinical trials for AD and Friedreich ataxia (NCT01339884, NCT01504854, NCT00743743, NCT00678431). Therapeutic implications derived from this work may be potentially extended to other diseases such as multiple sclerosis, 65 amyotrophic lateral sclerosis 66 and some forms of HSP such as SPG7, 54 which share axonal degeneration as a primary component of clinical disability and oxidative stress/mitochondria impairment as the primary or early contributing pathogenic factors. Mouse strains.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to Paraplegin, the groups of de Strooper and Scorrano have shown that mice lacking PARL have reduced cleavage of Opa1, indicating a requirement for PARL activity in the maturation of Opa1 [96]. Comparing Opa1 processing and mitochondrial morphology between Opa1 and Paraplegin deficient mice [100] will show which protein is the major processor for Opa1. Parapelgin, however, has also been implicated in the proper ribosome assembly in mitochondria [101] and reduction of paraplegin can also induce complex 1 deficiency and sensitivity to oxidative stress [102].…”
Section: Mitochondrial Fusion Proteinsmentioning
confidence: 95%
“…Primary MEFs were established from E14.5 embryos derived from intercrosses of time-mated Spg7 ϩ/ϩ or Spg7 Ϫ/Ϫ mice and immortalized by SV40 transformation (Ferreirinha et al, 2004). RNA interference (RNAi)-mediated down-regulation of gene expression was performed using specific Stealth RNAi and the nontargeting Stealth RNAi Negative Control (Invitrogen).…”
Section: Cell Culture and Down-regulation Of Afg3l1 And Afg3l2mentioning
confidence: 99%
“…Paraplegin E575Q was processed as efficiently as wildtype paraplegin upon mitochondrial import (Supplemental Figure S1). To exclude a role of preexisting, endogenous paraplegin for maturation, we isolated mitochondria from liver derived from paraplegin-deficient Spg7 Ϫ/Ϫ mice (Ferreirinha et al, 2004). The absence of paraplegin within mitochondria did not impair the import and processing of 35 S-labeled paraplegin, which occurred to a similar extent in Spg7 ϩ/ϩ and Spg7 Ϫ/Ϫ liver mitochondria (Supplemental Figure S1).…”
Section: Maturation Of Paraplegin Can Occur Upon Assembly Into M-aaa mentioning
confidence: 99%